2009
DOI: 10.1111/j.1743-6109.2008.00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Frequency and Range of Sexual Behavior in a Patient with Parkinson’s Disease After Use of Pramipexole: A Case Report

Abstract: Introduction Several recent reports have linked the use of dopamine agonists (DAs) to a variety of compulsive behaviors in patients with Parkinson’s disease (PD). These inappropriate behaviors may include pathological gambling, compulsive shopping, and hypersexuality. Aim To report the case of a patient with increased range of sexual behavior after use of pramipexole, a DA. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 24 publications
0
24
0
2
Order By: Relevance
“…In doing so, I will draw inferences from other case studies that I regard as analogous to this one in relevant respects: the aforementioned Schüpbach cases, a study by Munhoz et al (ref 12,. cit.…”
Section: A Patient's Dilemma: Choosing Between Mental Competence and mentioning
confidence: 99%
“…In doing so, I will draw inferences from other case studies that I regard as analogous to this one in relevant respects: the aforementioned Schüpbach cases, a study by Munhoz et al (ref 12,. cit.…”
Section: A Patient's Dilemma: Choosing Between Mental Competence and mentioning
confidence: 99%
“…In recent years, hypersexuality has been increasingly reported in association with hyperdopaminergic state in patients with PD; specifically, different studies have identified the association of hypersexuality with dopamine agonists [18,19] and levodopa treatment [8]. Approximately 2.2-8.3% of patients with PD taking Levodopa, Pramipexole, or Selegiline can develop hypersexuality according to preliminary studies [7,[20][21][22][23][24]. It is important that treating clinicians are aware of the extent of these pathological behaviours in the PD population and are able to correctly recognise them in order to implement appropriate management strategies and therefore limit potential harm to patients and society.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies, in both animals and humans, have demonstrated beneficial cognitive effects of pro-dopaminergic agents on measures of attention and working memory (Costa et al, 2009;Granon et al, 2000;Mattay et al, 2000;Mehta et al, 2000), there have also been reports of rare but concerning side effects, including induced impulse-control disorders in individuals with no prior history of such difficulties (Dodd et al, 2005;DriverDunckley et al, 2007;Giovannoni et al, 2000;Klos et al, 2005;Madden et al, 2010;McKeon et al, 2007;Munhoz et al, 2009;Potenza et al, 2007;Riba et al, 2008;Voon et al, 2006b;Weintraub et al, 2006). For example, the DA D2/D3 receptor agonist, pramipexole, as well as other DA receptor agonists have been implicated in the emergence of risk-seeking behaviors, such as pathological gambling in multiple case reports and cross-sectional studies in patients with Parkinson's disease (PD) (Bodi et al, 2009;Dodd et al, 2005;Lader, 2008;Pontone et al, 2006;Potenza et al, 2007;Voon et al, 2006aVoon et al, , 2006bWeintraub et al, 2006Weintraub et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%